2019
DOI: 10.1055/s-0039-1696946
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Supplementation and Its Indications

Abstract: Adequate plasma levels of fibrinogen are essential for clot formation, and in severe bleeding, fibrinogen reaches a critically low plasma concentration earlier than other coagulation factors. Although the critical minimum concentration of fibrinogen to maintain hemostasis is a matter of debate, many patients with coagulopathic bleeding require fibrinogen supplementation. Among the treatment options for fibrinogen supplementation, fibrinogen concentrate may be viewed by some as preferable to fresh frozen plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 86 publications
0
28
0
1
Order By: Relevance
“…22 Depletion is associated with poor outcomes, an effect which can be reversed with supplementation. 41 Low fibrinogen concentrations correlate with increased transfusions, ventilator days, and increased early and late mortality. 42 Fibrinogen supplementation improves clot initiation and stability, 43,44 and may decrease mortality in this group.…”
Section: Current Under S Tand Ing Of the Mechanis Ms Of Tr Auma-indmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Depletion is associated with poor outcomes, an effect which can be reversed with supplementation. 41 Low fibrinogen concentrations correlate with increased transfusions, ventilator days, and increased early and late mortality. 42 Fibrinogen supplementation improves clot initiation and stability, 43,44 and may decrease mortality in this group.…”
Section: Current Under S Tand Ing Of the Mechanis Ms Of Tr Auma-indmentioning
confidence: 99%
“…Coagulopathic patients can harbor hypofibrinogenemia early after injury, which can be a marker of TIC, and is dose‐dependently related to shock, injury severity, and mortality . Depletion is associated with poor outcomes, an effect which can be reversed with supplementation . Low fibrinogen concentrations correlate with increased transfusions, ventilator days, and increased early and late mortality .…”
Section: Current Understanding Of the Mechanisms Of Trauma‐induced Comentioning
confidence: 99%
“…Fibrinogen plays a central role in hemostasis as the substrate by which clots are formed. Deficiencies of a congenital or acquired nature have significant morbidity and mortality effects, and therefore supplementation is required in these patients [105 , 106] . Plasma and cryoprecipitate have both been used as replacement therapies for decades, but neither of these is ideal, requiring large volumes (less so in cryoprecipitate), risking pathogen infection, and requiring lengthy thawing [107 , 108] .…”
Section: The Uses Of Clotting Factor Concentrate In Hematologic Diseamentioning
confidence: 99%
“…The importance of detecting and treating hypofibrinogenemia early was also investigated in a prospective cohort study of 517 adult trauma patients (42). Multiple studies have demonstrated evidence that hypofibrinogenemia is a critical issue in severe bleeding for pediatric intraoperative and trauma patients (43)(44)(45). One study in pediatric trauma patients analyzed an institutional transfusion protocol where cryoprecipitate was not included until the third transfusion package.…”
Section: Goal-directed Hemostatic Resuscitationmentioning
confidence: 99%